Sistematización del uso de equipos de laboratorio de construcciones rurales de la facultad de Ciencias Agropecuarias. Universidad Nacional de Trujillo. La Libertad 2018 - Rodriguez Carril, Alberto Jampier (2019)
The systematization, order, norms, parameters are part of a process that aim to allow better results. Even more so when it comes to tests of vital importance for multiple engineering projects as required. To carry out a systematization process for the use of laboratory equipment, it is precisely this: to establish an order or classification. The idea is very clearly related to scientific and / or academic research spaces. The laboratory of rural constructions of the faculty of agricultural sciences. It has materials and equipment, however they were limited at the time of performing the dictation of the chair and carrying out research experiments, scientific or technical work. As part of this process, a documentary record of the goods and other objects (inventory) was carried out, thus giving details on the data capture. Also using their proper labeling of all of them, thus issuing a clear visual message for immediate understanding. On the other hand, also took into account the recommendations of the jury and as part of the development of training, make a guided incorporation to the facilities of the soil mechanics laboratory of the national agricultural university La Molina. Joining your work routine and thus be able to take into account many details and knowledge. Which subsequently allowed cascading transmission of the information and experience acquired. Said also of the academic material provided. The information corresponding to the equipment was also requested at the school address (file). We were provided with the manuals, which were in foreign language (English) for translation and documentation as part of this systematization process.